Responses to the agricultural crisis in the Marco del Jerez area at the end of the 19th century: a case study - Vázquez-Fariñas, María (My University, 2022)
Historically, the wine business has been one of the main economic activities developed in the province of Cadiz (Andalusia, Spain), gaining special relevance since the midnineteenth century, a period characterized by growth and prosperity in the sector. However, towards the end of that century, the arrival of a major crisis in the Andalusian wine sector brought serious difficulties for the wine companies in the region. Therefore, the aim of this paper is to study how the wine companies of the Marco del Jerez area (Andalusia, Spain) behaved in the face of this crisis in the sector that occurred at the end of the 19th century. To this end, a case study is presented: that of the Cadiz company Lacave & Co.; and an analysis is made of how this company reacted to the external forces that forced it to transform its structure, its objectives and the strategies developed until then, adapting its management practices to a changing environment. Based on the analysis of the company's books, accounting records, documentation preserved in the notarial protocols of the city of Cadiz and other publications of the time, the aim is to learn how this company adapted to the new market circumstances and the effectiveness of the measures adopted to overcome the crisis. This is a very important topic in economic history and the history of the company, since understanding how large companies faced crises in the past can help us to adopt strategies that allow us to improve companies nowadays and solve current and future economic problems.
Keywords: Agricultura - Historia; Jerez de la Frontera; Agricultural crisis; Marco del Jerez; Wine; 19th century; Lacave & Company